Menilik “Tilik”: Representasi Citra Perempuan Dalam Transformasi Ruang Virtual - Putri, Addin Kurnia; Wibisono, Gunawan (Journal of Politics and Democracy, 2022)
As part of popular culture products, movies play an important role in shaping images and representations in social life. A movie always captures the social reality that develops in society. Exploring the meaning of movie texts can be done from various perspectives. "Tilik" is one of the popular short films on the YouTube channel. In general, this film tells the story of how the culture of rural communities that have mechanical solidarity, which is solidarity that emphasizes the state of collective consciousness, transforms social space. This research analyzes the film "Tilik" with the concept of representation and transformation of virtual space. The representation of women's image is seen in the movie "Tilik", including the vulnerability of women's work, marriage standards, and the illusion of beauty. At the same time, the transformation of virtual space occurs in rural communities, which experience a shift in social space by using the internet and social media.